Neurocognitive deficits after botulism: a clinical case series study - Rosenqvist, Laura; Sandvei, Charlotte; Skarphedinsson, Sigurdur (Frontiers in Neurology, 2024)
Purpose This case study examined long-term cognitive deficits after botulism. Only a very limited number of studies on post-acute cognitive impairment after botulism exist, and data are incomplete. Method A semi-structured interview on long-term cognitive consequences of botulism was conducted for six family members, who contracted the infection after ingestion of lumpfish-roe 2.5 years ago. Two of the family members underwent neuropsychological assessment of attention, memory, and executive functioning as well. Finding Results of the semi-structured interviews showed individual subjective cognitive deficits across processing speed, attention, concentration, short-and long-term memory, and executive functioning. Test results showed mild cognitive impairment in attention and mild–moderate deficits in executive functioning. Conclusion These results support previous findings that patients of various infectious diseases may suffer unspecific long-term neurocognitive deficits. Assessment and initiation of relevant post-acute treatment and rehabilitation might be central to prognosis, functional ability, and psychological well-being.